Strategi Efektif Dalam Manejemen Organisasi Pendidikan Untuk Meningkatkan Kualitas Pembelajaran - Razak, Abdur; Aulia, Dahlia; Augydia, Nakita; Nasution, Rabiah; Nasution, Inom (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Education continues to develop from time to time, educational organization management has an important role in directing, managing and improving the quality of learning in various educational institutions. The effectiveness of educational management plays a role in optimizing the use of human resources, directing goals, and overcoming challenges that arise in the world of education. This research aims to improve the quality of learning, as well as the challenges and obstacles in implementing effective strategies. This research uses library research methods. The results of this research show that an effective strategy in education management is to improve the quality of learning by developing integrated learning plans, evaluating the learning process, developing the quality of educators, and developing an inclusive learning environment. Challenges and obstacles in implementing effective strategies result from a lack of adequate resources and infrastructure.